Performance Evaluation of Selected Food Processing Companies through Value Added Statements - Dadhaniya C Abhisha; Rathod K Anjali (Journal of Social Commerce, 2022)
Along with the conventional technique of measuring financial success, economists and other professionals are also evaluating a firm's development and survival using a value-added statement (VAS). The purpose of this research study is to quantify, assess, and compare the performance of value-added statements and value-added ratios in two food processing firms, LT Foods Ltd. and KRBL Ltd., during a five-year period from 2015 to 2019. The different value-added ratios such as Net Value Added to Total Revenue, Employee Benefits to Net Value Added, Government Shares to Net Value Added, Capital Providers to Net Value Added, and Retain Earnings to Net Value Added are employed. After examining the development of all value-added ratios, it is determined that KRBL Ltd.'s average performance is constant in comparison to LT Foods Ltd. To compare the means of these various value-added ratios, a statistical T-test with a 5% threshold of significance is applied. The analysis revealed that the null hypothesis is accepted for all value-added ratios except Capital Provider to Net Value Added. This suggests that throughout the research period, there was no significant difference in the value-added ratios of LT Foods Ltd. and KRBL Ltd.